Drunk driving : an opposing viewpoints guide - Friedman, Lauri S. (Writing the critical essay, 2008)
Explores differing views on drunk driving and uses the opposing viewpoints format to increase proficiency in writing critical essays, with emphasis on organizing ideas and arguments in the five-paragraph essay